The family of glutathione peroxidase proteins and their role against biotic stress in plants: a systematic review - do Carmo Santos, Maria Luíza; Silva Santos, Ariana; Pereira Silva de Novais, Diogo; dos Santos Lopes, Natasha; Pirovani, Carlos Priminho; Micheli, Fabienne (Frontiers in Plant Science, 2025)
IntroductionGlutathione peroxidases (GPXs) are extensively studied for their indispensable roles in eliminating reactive oxygen species by catalyzing the reduction of hydrogen peroxide or lipid peroxides to prevent cell damage. However, knowledge of GPXs in plants still has many gaps to be filled. Thus, we present the first systematic review (SR) aimed at examining the function of GPXs and their protective role against cell death in plants subjected to biotic stress.MethodsTo guide the SR and avoid bias, a protocol was developed that contained inclusion and exclusion criteria based on PRISMA guidelines. Three databases (PubMed, Science Direct, and Springer) were used to identify relevant studies for this research were selected.ResultsA total of 28 articles related to the proposed objective. The results highlight the importance of GPXs in plant defense against biotic stress, including their role in protecting against cell death, similar to the anti-apoptotic GPXs in animals. Data from gene expression and protein accumulation studies in plants under various biotic stresses reveal that GPXs can both increase resistance and susceptibility to pathogens. In addition to their antioxidant functions, GPXs act as sensors and transmitters of H2O2 signals, integrating with the ABA signaling pathway during stress.DiscussionThese findings show that GPXs delay senescence or reinforce physical barriers, thereby modulating resistance or susceptibility to pathogens. Additionally, their functions are linked to their cellular localization, which demonstrates an evolutionary relationship between the studied isoforms and their role in plant defense. This information broadens the understanding of molecular strategies involving GPX isoforms and provides a foundation for discussions and actions aimed at controlling necrotrophic and/or hemibiotrophic pathogens.